2012
DOI: 10.1111/j.1349-7006.2012.02272.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol enhances radiation sensitivity in prostate cancer by inhibiting cell proliferation and promoting cell senescence and apoptosis

Abstract: Radiation therapy (XRT) for treatment of localized prostate cancer (PCA) has outcomes similar to surgery and medical therapy. Toxicities of XRT and the relative radioresistance of PCA limit the effectiveness of this treatment method. Safe and effective radiosensitizing agents are lacking to enhance the effectiveness for XRT for PCA. In this study, the effect of XRT in combination with the radiosensitizing agent resveratrol (RSV) was investigated in a radioresistant PCA cell line, PC-3. Our results show the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 49 publications
(147 reference statements)
12
89
0
Order By: Relevance
“…Various antitumor effects of Res have been described previously, including the inhibition of DNA polymerase, protein kinase C, cyclooxygenase-2 or interleukin-6 activities, and the suppression of transcription factors such as nuclear factor-κB (4,11,12,21,22). The present study revealed that Res increased autophagosome formation, decreased cell viability and induced apoptotic death in drug-resistant K562/ADM cells.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Various antitumor effects of Res have been described previously, including the inhibition of DNA polymerase, protein kinase C, cyclooxygenase-2 or interleukin-6 activities, and the suppression of transcription factors such as nuclear factor-κB (4,11,12,21,22). The present study revealed that Res increased autophagosome formation, decreased cell viability and induced apoptotic death in drug-resistant K562/ADM cells.…”
Section: Discussionsupporting
confidence: 70%
“…Res has been shown to induce cell death through various mechanisms in different cancer cell lines (2,11,12,19). Various antitumor effects of Res have been described previously, including the inhibition of DNA polymerase, protein kinase C, cyclooxygenase-2 or interleukin-6 activities, and the suppression of transcription factors such as nuclear factor-κB (4,11,12,21,22).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the human malignant B cells, the principle mechanism of resveratrol is to induce the cell apoptosis by activating apoptosis protease-3 and p38 protein kinase pathways. Another mode of resveratrol-induced cell apoptosis follows the paradigm of activating apoptotic protease-2 via a special mechanism in mitochondria (10,16,17). Activated apoptotic protease-2 triggers the conformational change in the Bax/Bak with the release process of mitochondria cytochrome C, apoptosis-inducing factor (AIF) and endonuclease G.…”
Section: Natural Products and Apoptosis-related Signaling Moleculesmentioning
confidence: 99%
“…12 Furthermore, resveratrol has been shown to enhance radiation sensitivity in a variety of other malignancies, including melanoma, prostate cancer, and non-small lung cancer. [13][14][15] In the present study, we sought to determine the effects of resveratrol on arsenic trioxide-induced antileukemic responses. We were particularly interested in examining whether resveratrol can potentiate arsenic trioxide-induced autophagy or apoptosis, as our recent studies have established that in addition to apoptotic cell death, induction of autophagy is a key mechanism for the generation of arsenic-induced antileukemic effects on primary leukemic precursors.…”
Section: Introductionmentioning
confidence: 99%